CASE REPORT OF EARLY-DIABETES HYPOGLYCEMIA: LINK BETWEEN REACTIVE HYPOGLYCEMIA AND INSULIN RESISTANCE - Asmara, Oke Dimas; Tahapary, Dicky Levenus; Wisnu, Wismanandari; Yunir, Em (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypoglycemia rarely occurs in patients not being treated for diabetes mellitus. To this end, further investigation needs to be done to find the underlying cause of hypoglycemia, thus, determining appropriate treatment. CASE A 62-year-old man (weight: 46 kg, BMI: 18.8 kg/m2 ) was referred for recurrent hypoglycemia within the last 4 months. There was no history of gastric bypass surgery nor consumption of hypoglycemic agent. Laboratory examination taken during a hypoglycemic episode (blood glucose of 40 mg/dL) revealed elevated serum insulin and C-peptide levels, which were 38.6 (NV 2.6-24.9) uU/ mL and 8.73 (NV 1.1-4.4) respectively. Neither abdominal ultrasound, endoscopic ultrasound, abdominal CT scan nor MRI revealed a mass in the pancreas or other organs in the abdomen. Following the given complex carbohydrates, the patient could finish extended oral glucose tolerance test (eGTT) and the result was 97 mg/dL. Following 1-2 hour administration of 75 g anhydrous glucose, patient’ blood glucose levels were 244 and 203 mg/dl, respectively. Hypoglycemia occurred after 4 hours eGTT (48 mg/dL). CONCLUSION Approach to hypoglycemia in patients not treated with diabetic medication is a challenging issue for clinicians. The first step is to confirm the presence of hypoglycemia. Second is to measure the serum levels of insulin and C-peptide during a hypoglycemic episode. However, reactive/ functional hypoglycemia can be found in early diabetes mellitus. Extended/prolonged oral glucose tolerance test should be considered in a patient suspected to have reactive hypoglycemia.